Modus Penipuan Berkedok Giveaway di Era Digital: Cara Mengenali dan Menghindarinya - Ida Ayu Parami Cintiya; Ni Putu Rai Yuliartini; Dewa Gede Sudika Mangku (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The giveaway phenomenon in the digital era has become a popular strategy to increase interaction on social media. However, this popularity is also used by irresponsible individuals to commit fraud under the guise of giveaways. This article aims to identify the modus operandi of giveaway fraud, provide guidance on recognizing the characteristics of fraud, and present preventive measures to avoid it. The methods used include literature review of digital fraud cases, analysis of cybercrime patterns, and interviews with digital literacy experts. The results show that the fraud mode often uses fake accounts that resemble official organizers, asks for personal information or payment of certain fees, and offers rewards that are too fantastic to lure victims. Low digital literacy is one of the main factors in the high number of victims of this fraud. By raising public awareness through education about the characteristics of fraud and methods of verifying information sources, the potential for victims can be minimized. In conclusion, systematic prevention efforts and active participation of the community in disseminating related information are important to protect internet users from the threat of giveaway fraud. This article recommends improving digital literacy programs and strengthening regulations against cybercrime as a long-term step.